PENERAPAN PROBLEM BASED LEARNING DENGAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN HASIL BELAJAR - Laila Lutfiana; Muhammad Aunur Rofiq; Fulusia Nurmawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This classroom action research was initiated to optimize IPAS academic outcomes, teaching competencies, and student engagement inside grade IV at SDN 2 Pelem, specifically focusing on the theme